2020
DOI: 10.1080/2331186x.2020.1817253
|View full text |Cite
|
Sign up to set email alerts
|

Maltese teachers’ beliefs concerning the integration of children’s literature in mathematics teaching and learning

Abstract: This exploratory mixed-methods study set out to explore Maltese primary school teachers' perceived barriers to, and enablers for, the integration of children's literature in mathematics teaching. Data were collected by means of an online questionnaire and semi-structured interviews, and analysed thematically using Ajzen's Theory of Planned Behaviour. The responses given by the participants showed that integration of mathematics and stories was not a common practice. The perceived barriers were categorised as R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 25 publications
2
20
0
2
Order By: Relevance
“…Our Australian study's findings largely resonate with those of the Irish study (Prendergast et al, 2019) and the Maltese study (Farrugia & Trakulphadetkrai, 2020). Specifically, the contextual data of the teachers in this study revealed that the majority of them (75.1%) had either never used children's literature in their mathematics teaching or had done so but infrequently (i.e., 10 mathematics lessons or less per school year).…”
Section: Comparison Of Findingssupporting
confidence: 78%
See 4 more Smart Citations
“…Our Australian study's findings largely resonate with those of the Irish study (Prendergast et al, 2019) and the Maltese study (Farrugia & Trakulphadetkrai, 2020). Specifically, the contextual data of the teachers in this study revealed that the majority of them (75.1%) had either never used children's literature in their mathematics teaching or had done so but infrequently (i.e., 10 mathematics lessons or less per school year).…”
Section: Comparison Of Findingssupporting
confidence: 78%
“…There is a limited body of research that connects teachers' beliefs to the use of children's literature in the teaching of mathematics (e.g., Cotti & Schiro, 2004;Farrugia & Trakulphadetkrai, 2020;Prendergast et al, 2019). In Cotti and Schiro's (2004) study, they created a Mathematics and Children's Literature Belief Inventory to facilitate teachers' understanding of their own ideological positions and those of other teachers.…”
Section: Use Of Children's Literature In Mathematics Teachingmentioning
confidence: 99%
See 3 more Smart Citations